Opportunities and barriers for niche marketing of lamb in European LFAs based on consumer attitudes to product quality - Gerold Rahmann; Stuart W. Ashworth; Jean-Pierre Boutonnet; Gianluca Brunori; Ioannis Papadopoulos (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
With commodity prices continuing to decrease and with policy constraint that farmers cannot easily increase their incomes by increasing volumes of production, they must find alternative ways to maintain their standard of living. This can be achieved by either niche marketing of agricultural products or by environmental payments, which are paid by either the government or the consumer. The results of a consumer survey carried out in Less Favoured Areas in Scotland, Germany, Greece, France and Italy to assess consumer attitudes of what constitutes the quality of lamb and the extent to which this provides an opportunity to exploit niche marketing, are discussed. Consumers generally have much less interest in the use of regional labelling, ecologically friendly production systems or the linkage of landscape and production systems in the buying decision. It is concluded that potential exists to develop niche markets for lamb and that these niches demonstrate significant regional differences. Equally, however, it is concluded that there are only limited rewards for production systems which are sympathetic to the environment. To achieve this goal, policy intervention is required, geared directly to environmental management practices. Future policy support towards farmers in LFAs is needed as a mix of policy instruments. Nowadays, financial support of farming in LFAs is necessary to grant farmers income, but structural support (e. g. in marketing products under reliable labelling towards consumers' requests with trust in the "added values") can help to increase LFA-farmers income without increasing subsidies.
Keywords: 330; Schaffleisch; Fleischmarkt; Nischenstrategie; Konsumentenverhalten; Marktforschung; Schottland; Deutschland; Griechenland; Frankreich; Italien